Pengaruh Kualitas Layanan dan Harga terhadap Kepuasan Konsumen pada Depot Air Minum Isi Ulang UD Enzes Pengabean - Nur Kiman; Slamet Bambang Riono; Muhammad Syaifulloh; Akbar NP Darma Wahana; Gian Fitralisma (Program Studi Manajemen Universitas Muhadi Setiabudi, 2019)
This study aims to determine and analyze the effect of service quality and price on consumer satisfaction at UD refill drinking water depots. Enzes Pengbean. The population in this study are consumers who visit and are regular customers of the UD refill drinking water depot. Enzes at Pengabean, numbering around 400 people, were taken from 2019 data using purposive sampling. With the results of the research showing that service quality has a significant effect on customer satisfaction at the UD Refill Drinking Water Depot. Enzes was 40.3%, and prices had a significant effect on consumer satisfaction at the UD Refill Drinking Water Depot. Enzes, amounting to 43.3%. With a value of Fcount > Ftable (28.325 > 2.70), Service Quality and Price simultaneously or simultaneously have a significant effect on Consumer Satisfaction at UD refill drinking water depots. Reliability and determinant value (R2) of 0.472 or 47.2% This high enough value indicates that other factors not included as variables in this study have less ability to explain consumer satisfaction at UD refill drinking water depots. Enzes Pengbean